Analisis Tindak Tutur Ekspresif dalam Film Sumala Karya Riheam Junianti: An Analysis of Expressive Speech Acts in the Film "Sumala" by Riheam Junianti - Muhammad Hayat Qais; Suleha Suleha; Muhammad Hanafi; Yusmah Yusmah (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
This study aims to analyze the function of expressive illocutionary speech acts in the film Sumala by Riheam Junianti. This study is motivated by the importance of expressive speech acts in conveying characters' feelings, attitudes, and emotional responses, which play a role in building the storyline and social relationships among characters in the film. The study uses a qualitative, descriptive approach. The research data consist of the characters' expressive speech acts, and the data source is the film Sumala, produced by Hitmaker Studios and broadcast on Netflix. Data collection was carried out through listening and note-taking, with careful observation of the dialogue, expressions, and context of the conversation. Data analysis was carried out in three stages: data reduction, data presentation, and conclusion. The results of the study show that there are six functions of expressive speech acts in the dialogue of the film Sumala, namely blaming, criticizing, apologizing, thanking, complaining, and praising. Of all the data found, blaming is the most dominant form, with 14 data, followed by criticizing with 8, apologizing with 5, thanking with 3, complaining with 2, and praising with 1. The dominance of the blaming function indicates the strength of the conflict and emotional tension built into the film. The findings of this study indicate that expressive speech acts play a crucial role in representing the characters' psychological states, establishing the story's atmosphere, and clarifying the meaning and social relationships embedded in the film's dialogue.